Application of the Martel dynamic hardness to the penetration problem - Milman, Yu.V.; Goncharuk, V.A.; Mordel L.V. (Электронная микроскопия и прочность материалов, 2012)
Penetration of the undeformable kinetic energy projectile (KEP) into the target is considered as the “deep” indentation. It was shown by the example of aluminum alloys that the Martel dynamic hardness HMRd can be used for description of this process.